The peopling of South America and the trans-Andean gene flow of the first settlers - Gómez-Carballa, Alberto; Pardo-Seco, Jacobo; Brandini, Stefania; Achilli, Alessandro; Perego, Ugo A.; Coble, Michael D.; Diegoli, Toni M.; Álvarez-Iglesias, Vanesa; Martinón-Torres, Federico; Olivieri, Anna; Torroni, Antonio; Salas, Antonio (Genome Research, 2018)
Genetic and archaeological data indicate that the initial Paleoindian settlers of South America followed two entry routes separated by the Andes and the Amazon rainforest. The interactions between these paths and their impact on the peopling of South America remain unclear. Analysis of genetic variation in the Peruvian Andes and regions located south of the Amazon River might provide clues on this issue. We analyzed mitochondrial DNA variation at different Andean locations and >360,000 autosomal SNPs from 28 Native American ethnic groups to evaluate different trans-Andean demographic scenarios. Our data reveal that the Peruvian Altiplano was an important enclave for early Paleoindian expansions and point to a genetic continuity in the Andes until recent times, which was only marginally affected by gene flow from the Amazonian lowlands. Genomic variation shows a good fit with the archaeological evidence, indicating that the genetic interactions between the descendants of the settlers that followed the Pacific and Atlantic routes were extremely limited.